Optimization of Growth Medium and Fermentation Conditions for the Production of Laccase3 from Cryphonectria parasitica Using Recombinant Saccharomyces cerevisiae. Issue 4 (2nd October 2019) - Jeong, Yong-Seob; So, Kum-Kang; Lee, Ju-Hee; Kim, Jung-Mi; Chun, Gie-Taek; Chun, Jeesun; Kim, Dae-Hyuk
Abstract: Statistical experimental methods were used to optimize the medium for mass production of a novel laccase3 (Lac3) by recombinant Saccharomyces cerevisiae TYEGLAC3-1. The basic medium was composed of glucose, casamino acids, yeast nitrogen base without amino acids (YNB w/o AA), tryptophan, and adenine. A one-factor-at-a-time approach followed by the fractional factorial design identified galactose, glutamic acid, and ammonium sulfate, as significant carbon, nitrogen, and mineral sources, respectively. The steepest ascent method and response surface methodology (RSM) determined that the optimal medium was (g/L): galactose, 19.16; glutamic acid, 5.0; and YNB w/o AA, 10.46. In this medium, the Lac3 activity (277.04 mU/mL) was 13.5 times higher than that of the basic medium (20.50 mU/mL). The effect of temperature, pH, agitation (rpm), and aeration (vvm) was further examined in a batch fermenter. The best Lac3 activity was 1176.04 mU/mL at 25 °C, pH 3.5, 100 rpm, and 1 vvm in batch culture.